The Correlation of Cholinesterase Enzyme Activities Based on Age in Male Farmers - Prasanti Prasanti; Tri Harningsih (Indonesian Journal of Global Health Research, 2022)
The use of pesticides to control plant pests can have an adverse impact on the health of farmers and the surrounding environment. Pesticides enter the body through the respiratory tract and unprotected skin. Pesticide poisoning can cause a decrease in cholinesterase enzyme activity in the blood which can cause death. The purpose of this study was to determine whether there was a relationship between cholinesterase enzyme activity based on age in male farmers in Kadibolo Village, Klaten Regency. This type of research is analytic observational. The sampling method used was simple random sampling technique. This study used a cross sectional study design with a sample of 20 farmers. Samples were taken from farmer’s venous blood and stored in a vacuum tube without yellow anticoagulant then centrifuged to collect serum. Measurement of cholinesterase enzyme activity using Roche Cobas c 501. The variables of this study were age and cholinesterase enzyme activity of male farmers in Kadibolo Village. The results of statistical tests with SPSS using Fisher's exact test obtained p value = 0.447, RP value = 0.333 and 95% CI = 0.025-4.401. There is no relationship between cholinesterase enzyme activity and age in male farmers in Kadibolo Village.